История контент-анализа: версии и безмолвствующие импликации - Осин, В. (Інститут історії України НАН України, 2008)
The status of content analysis in modern scientific discourse is practically indisputable. It is here that the danger is hidden: being in the beginning easy to identify and undoubtedly new m ethod, in future content analysis seized to be both purely quantitative and exceptionally modern: the number of its variations is countless and its main elements can be found as far back as ancient times. Thus, the determination of the degree of scientific validity of content analysis in contemporary circumstances presupposes the deconstruction of its practice of history -writing as the first step. It must help to find out the actual factors that have made content analysis the established scientific method.